The Effect of Teaching Reading Aloud Technique in Improving English Pronunciation - Putri Wahyuni (General English Education, 2022)
Pronunciation is one of the essential components in oral form and is considered the basic ability of speaking English as well as other languages that has to be learnt by the students. Pronunciation is the production of sounds that is used for making meaning. The correct pronunciation of English is very important because the target of learning English is to help students to speak accurately and fluently which leads them easy to understand the utterances and to produce intelligible sounds. Reading aloud is an activity to read something loudly. By reading aloud, students can test themselves whether the pronunciations that they are saying is correct or not. This research was conducted to know the effect of teaching reading aloud technique in improving English Pronunciation. This research used “One Group Pretest and Posttest Design”. The sample of this research was the ninth-grade students by taking 31 students (13 male and 18 female). The result showed that the calculation of Wilcoxon Signed-Rank Test was 0.000. Since 0.000 < 0.05 even <0.001, the null hypothesis was rejected. In other words, there is a significant effect on students’ pronunciation of English by teaching using reading aloud technique.